Underrepresentation of developing country researchers in development research. Issue 17 (7th October 2022) - Amarante, Verónica; Burger, Ronelle; Chelwa, Grieve; Cockburn, John; Kassouf, Ana; McKay, Andrew; Zurbrigg, Julieta
ABSTRACT: We present evidence of how researchers from developing countries are represented in three areas of research: conference presentations, articles in journals, and citations. We find that the bulk of research on development and development policies in the South is conducted by researchers from the North. Southern universities represents 9% of conference presenters, while 57% of conference presenters are from Northern universities. There has been no evidence of improvements over time. Fewer than one in six of the articles published in top 20 development journals from 1990 to 2019 were by Southern researchers, while close to three-quarters were by Northern researchers. The remaining 11% were collaborations by Southern and Northern researchers. Additionally, there are also fewer citations per article for Southern-authored articles than for Northern-authored articles.